2009
DOI: 10.1016/j.ympev.2009.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogenetics reveals extreme morphological homoplasy in Brazilian worm lizards challenging current taxonomy

Abstract: Amphisbaenians are fossorial squamate reptiles distributed mainly in South America and Africa. Brazilian worm lizards belong to the family Amphisbaenidae, which has far more recognized species than any of the other five amphisbaenian families. Morphological datasets recovered Amphisbaenidae as paraphyletic, while previous molecular phylogenetic studies did not include enough taxa to solve the generic-level relationships within this family. We present a molecular phylogenetic hypothesis based on a sample of 58 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
31
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 40 publications
3
31
0
5
Order By: Relevance
“…The family Amphisbaenidae contains about 175 species distributed in 11 genera (Uetz and Josek 2015), this number included the recently synonymized genus by Mott and Vieites (2009) into Amphisbaena (Anops, Aulura, Bronia, Cercolophia and Leposternon).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The family Amphisbaenidae contains about 175 species distributed in 11 genera (Uetz and Josek 2015), this number included the recently synonymized genus by Mott and Vieites (2009) into Amphisbaena (Anops, Aulura, Bronia, Cercolophia and Leposternon).…”
mentioning
confidence: 99%
“…The genus Amphisbaena Linnaeus, 1758 includes 107 species (Mott and Vieites 2009;Uetz and Josek 2015), with ten species known from Argentina. Amphisbaena heterozonata Burmeister, 1861, A. hiata Montero and Céspedez, 2002, A. mertensii Strauch, 1881, A. prunicolor (Cope, 1885), A. kingii (Bell, 1833) and A. microcephalum (Wagler, 1824 are known to occur in Corrientes province (Abdala et al 2012).…”
mentioning
confidence: 99%
“…Some studies tried to correlate the cranial variation with geography or phylogeny (Kearney, 2003;Mott & Vieites, 2009;Measey & Tolley, 2013). The present study suggested that these groups defined by cranial variation do not reflect the biogeographical distribution neither the phylogenetic relationship.…”
Section: Mott and Vieites (2009) Investigated The Phylogenetic Relationmentioning
confidence: 61%
“…Contrary to Mott and Vieites (2009), Ribeiro et al (2011), described a South American species, and revalidated the genus Leposternon, stating that the taxonomic changes on the Neotropical amphisbaenids were precipitated due to the low bootstrap supports and little morphological evidences. Although plausible, Ribeiro et al (2011) considered that the decision to synonymize the genus Leposternon to Amphisbaena needed more evidence.…”
Section: Mott and Vieites (2009) Investigated The Phylogenetic Relationmentioning
confidence: 99%
See 1 more Smart Citation